2014
DOI: 10.1007/s11606-014-2765-5
|View full text |Cite
|
Sign up to set email alerts
|

Brief Training of Student Clinicians in Shared Decision Making: A Single-Blind Randomized Controlled Trial

Abstract: BACKGROUND: Shared decision making is a crucial component of evidence-based practice, but a lack of training in the "how to" of it is a major barrier to its uptake. OBJECTIVE: To evaluate the effectiveness of a brief intervention for facilitating shared decision making skills in clinicians and student clinicians. DESIGN: Multi-centre randomized controlled trial. PARTICIPANTS: One hundred and seven medical students, physiotherapy or occupational therapy students undertaking a compulsory course in evidence-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
(38 reference statements)
0
64
1
7
Order By: Relevance
“…A tematização destas questões, assim como o treinamento clínico prático sob princípios da PCC, deve fazer parte da formação profissional. Mesmo intervenções educativas curtas (de poucas horas e, portanto mais facilmente incorporadas a currículos já estruturados) podem produzir resultados positivos nas habilidades e crenças sobre compartilhamento de decisões entre estudantes das profissões de saúde 21 . Em relação às barreiras no nível dos pacientes, problemas cognitivos, de expressão, de memória e de autopercepção são as mais frequentemente relatadas 22 .…”
Section: Desafios Para a Implantação Da Pccunclassified
See 1 more Smart Citation
“…A tematização destas questões, assim como o treinamento clínico prático sob princípios da PCC, deve fazer parte da formação profissional. Mesmo intervenções educativas curtas (de poucas horas e, portanto mais facilmente incorporadas a currículos já estruturados) podem produzir resultados positivos nas habilidades e crenças sobre compartilhamento de decisões entre estudantes das profissões de saúde 21 . Em relação às barreiras no nível dos pacientes, problemas cognitivos, de expressão, de memória e de autopercepção são as mais frequentemente relatadas 22 .…”
Section: Desafios Para a Implantação Da Pccunclassified
“…A implantação da PCC exige mudança na cultura das organizações e das profissões de saúde. Há diversos instrumentos de avaliação que podem ser usados para caracterizar o grau de "centralidade" no cliente, tanto no nível institucional, quanto no nível dos profissionais e dos pacientes individualmente 21,[23][24][25] . Por último, a formação de profissionais envolve investimentos financeiros, mas ao longo do tempo, os benefícios podem ultrapassar os custos 19 .…”
Section: Desafios Para a Implantação Da Pccunclassified
“…This was a two-institution, single-blinded randomized study, with 100 (93 % of eligible) interprofessional participants, including third-year medical students, final-year occupational therapy honors students, and postgraduate physiotherapy students. 10 Both study arms received a book chapter on shared decision making, and the intervention group additionally received a 1-h tutorial that included a five-step framework for communicating evidence and a facilitated critique of a pre-recorded modeled role-play on shared decision making. Two weeks later, all participants were paired and videotaped while performing role-plays of a physician-patient encounter that required evidence-based decision making.…”
Section: Theme 3: Interprofessional Educationmentioning
confidence: 99%
“…1 Since then, more than 80 randomized trials have been published, many demonstrating that involving the patient in decisions and improving provider communication are associated with positive healthcare quality markers and overall morbidity and mortality outcomes. 2 Few have involved multi-disciplinary practitioners; the trial by Hoffman et al 3 evaluated the effectiveness of a brief intervention on facilitating shared decision making (SDM) among student clinicians (of medicine, physiotherapy and occupational therapy) from two Australian universities.Based on valid, objective measures of video recorded interactions with simulated patient encounters, they found that their intervention improved performance of student healthcare providers in several important outcomes, including SDM communication skills, self-confidence in SDM skills, SDM attitudes and involving patients in decision making. An important limitation of this study is that it is based on simulated patients rather than live patients and the impact of the intervention was measured shortly after the intervention.…”
mentioning
confidence: 99%
“…1 Since then, more than 80 randomized trials have been published, many demonstrating that involving the patient in decisions and improving provider communication are associated with positive healthcare quality markers and overall morbidity and mortality outcomes. 2 Few have involved multi-disciplinary practitioners; the trial by Hoffman et al 3 evaluated the effectiveness of a brief intervention on facilitating shared decision making (SDM) among student clinicians (of medicine, physiotherapy and occupational therapy) from two Australian universities.…”
mentioning
confidence: 99%